2019
DOI: 10.1111/iju.14104
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term symptomatic outcome after transurethral resection of the prostate: A urodynamics‐based assessment

Abstract: Objectives To examine the long‐term outcomes of transurethral resection of the prostate. Methods We retrospectively collected the data of patients who had undergone transurethral resection of the prostate before December 2010. Patients had been evaluated by urodynamics and the International Prostate Symptom Score preoperatively, and they were re‐evaluated by using the International Prostate Symptom Score at the minimum 7 years after transurethral resection of the prostate. Patients who received any treatments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Data of a recent Cochrane and meta-analysis and of the RCT UPSTREAM study did not demonstrate the usefulness of preoperative urodynamics (UD) in these candidates to surgery [ 16 17 ]. However, several studies have shown that males with DUA, associated or not to BOO, had satisfactory results at short-time follow-up after surgery, but not long lasting-time [ 18 19 20 21 22 23 ]. Moreover, poorer surgical outcomes have been reported in underactive males than in non-underactive obstructed patients.…”
Section: Discussionmentioning
confidence: 99%
“…Data of a recent Cochrane and meta-analysis and of the RCT UPSTREAM study did not demonstrate the usefulness of preoperative urodynamics (UD) in these candidates to surgery [ 16 17 ]. However, several studies have shown that males with DUA, associated or not to BOO, had satisfactory results at short-time follow-up after surgery, but not long lasting-time [ 18 19 20 21 22 23 ]. Moreover, poorer surgical outcomes have been reported in underactive males than in non-underactive obstructed patients.…”
Section: Discussionmentioning
confidence: 99%
“…11,14 Post operatively; the effects of TUR-P can be assessed by follow up IPSS and uroflowmetry. 2,15 In this study setting; the protocol is patient after TUR-P is observed for a minimum of 5 days in hospital. On the fifth post-operative day the patient's catheter is removed and he is discharged after a successful trial of voiding per urethra.…”
Section: Discussionmentioning
confidence: 99%
“…Statistical analysis was performed with IBM-SPSS v. 17 2 the outcomes of males of group A and group B. After surgery, overall patient group, group A, and group B showed a significant improvement in IPSS score, Qmax, PVR, and BVE.…”
Section: Discussionmentioning
confidence: 99%
“…Although the results of these studies have been not completely concordant, most of them showed a general reversal of urinary symptoms back to the preoperative baseline, usually 7 years after surgery. 9,16,17 However, all these data concerns poor homogeneous samples, with different characteristics, such as detrusor overactivity, bladder outlet obstruction, the degree of detrusor contractility impairment. These differences make these studies difficult to compare with each other and with our research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation